Genomic Insights into Stutzerimonas kunmingensis TFRC-KFRI-1 Isolated from Manila Clam (Ruditapes philippinarum): Functional and Phylogenetic Analysis - Myunglip Lee; Sunghun Yi; Jiho Choi; Yukyoung Park; Chaehyeon Lim; Yucheol Kim (Microorganisms)
Stutzerimonas kunmingensis TFRC-KFRI-1, isolated from the gut of Manila Clam in the sediment of the West Sea of Korea, was investigated for its potential as a probiotic bacterium. This strain, belonging to the family Pseudomonadaceae, was previously classified as Pseudomonas kunmingensis but later reclassified to the genus Stutzerimonas, known for species with bioremediation and probiotic properties. To evaluate its genomic features and potential applications, we performed draft-genome sequencing and analysis. The genome of S. kunmingensis TFRC-KFRI-1 was assembled into a 4,756,396 bp sequence with a 62.8% GC content. Genomic analysis suggested potential genes for carbohydrate degradation and lactic acid production. The strain exhibited high average nucleotide identity (ANI) and 16S rRNA similarity with S. kunmingensis HL22-2T, further supporting its potential as a probiotic. This genome sequence provides valuable insights into the functional capabilities of S. kunmingensis TFRC-KFRI-1 and its potential applications in various industries, including aquaculture and food biotechnology. The genome sequence is available under GenBank accession number JBGJJB000000000.1, with related project information under BioProject PRJNA1147901 and Bio-Sample SAMN43173893.